The Roman stronghold at Nadleški hrib, Notranjska region - Laharnar, Boštjan (Arheološki vestnik, 2013)
This article deals with the Roman stronghold at Nadleški hrib in Loška dolina. It presents a plan of the site, the results of the geophysical surveys, a viewshed and analyses of energy-optimal pathways, and defines small archaeological finds. The Roman army chose to build the stronghold at Nadleški hrib because of its strategic position. We date the construction from Caesar’s administration of Cisalpine Gaul and Illyricum to the Augustan Period. The stronghold, therefore, played a role either during the Roman conquest or in the hinterland of the military conflicts in the Balkans during the Augustan Period.